Task Force for Business and Stability Operations : lessons from Afghanistan - Zimmerman, S. Rebecca; Egel, Daniel; Blum, Ilana (Research report (Rand Corporation), 2016)
"The Task Force for Business and Stability Operations (TFBSO), a multi-year endeavor for the U.S. Department of Defense, sought to use private-sector strategies to create sustainable economies in Iraq and Afghanistan. In this report, RAND researchers use semistructured interviews and both public and internal documentation to identify lessons from the Task Force's activities in Afghanistan, offering insights for similar projects in the future. The analysis describes the multitude of the Task Force's stakeholders resulting from its complex institutional status, plus the challenges that resulted from these diverse stakeholders. It uses a stakeholder-focused approach to explore several prominent TFBSO projects, informed by disparate stakeholder views. Ultimately, lessons identified from the Task Force's activities in Afghanistan fell under six categories: programmatic flexibility, leadership, measures of success, staffing, freedom of movement, and contracting. Because economic development is likely to remain a key component of U.S. contingency operations, policymakers can use the lessons identified in this report when planning and designing similar organizations in the future to find the right balance for success"--Publisher's web site